Manajemen Kepala Madrasah dalam Pengembangan Karir Guru di Madrasah Aliyah Negeri 5 Batanghari - Maula, Linziyatul; Jamilah, Jamilah; Elwiddah, Minnah (Dinasti Review, 2023)
The purpose of this research is to analyze the Management of Madrasah Principals in Teacher Career Development, this research was conducted at MAN 5 Batanghari. the variables used in this study were management, the role of the madrasah/school principal, and teacher career development. This research is descriptive and qualitative. data collection is used through observation, interviews, and documentation. The role of the Head of the Madrasa/school includes Educator, Manager, Administrator, Supervisor, Leader, Innovator, and Motivator. There are two types of teacher development, namely Career Development and Professional Development. So it can be concluded: 1) Management of Madrasah Heads in Teacher Career Development at Madrasah Aliyah Negeri 5 Batanghari; 2) Inhibiting Factors of Madrasah Principal Management in Teacher Career Development at Madrasah Aliyah Negri 5 Batanghari; and 3) Efforts Made by the Head of Madrasah in Developing Teacher Careers at Madrasah Aliyah Negeri 5 Batanghari.